Characterization of Traditional Market Solid Waste (TMSW) and Its Recycling Potential (Case Study : Traditional Markets in Bandar Lampung) - Muhammad Haviz; Dewi Agustina Iryani; Puspita Yuliandari; Udin Hasanudin; Elhamida Rezkia Amien; Agus Haryanto (The University of Lampung, 2022)
Solid waste has always been a problem for developing countries. In Bandar Lampung, the traditional market is the second largest contributor of solid waste, after households. Data for Traditional Market Solid Waste (TMSW) composition and generation rate in Bandar Lampung is rarely found, even though, data is needed to write the policy for TMSW management and its recycling potential. This research aims to provide data on TMSW composition, generation rate and chararacteristic in Bandar Lampung, also its recycling potential. The sample from 10 of 31 traditional markets in Bandar Lampung is collected for 8 consecutive days in morning and afternoon. Then, the sample was processed to obtain its composition, generation and density. 48.06% of TMSW compositions is donated by vegetable. Meanwhile, metal is rarely found in traditional markets, with only 0.37%. The average density of TMSW is 180.11 kg/m3, while Kangkung Market has the highest density with 237.84 kg/m3 and Cimeng Market has the lowest TMSW density with 123.07 kg/m3. The generation rate of TMSW is 53,602.35 kg/day. Biodegradable wastes from traditional markets in Bandar Lampung, with 53% water contents, can be potentially recycled by composting and/or anaerobic digester because of its economic value and characteristic. Keywords: Recycling, Solid Waste Management, Traditional Market Solid Waste, Waste Characterization